Shortening of muscle relaxation time after creatine loading - van Leemputte, M; Vandenberghe, K; Hespel, P (Journal of applied physiology (1985), 1999)
Department of Kinesiology, Faculty of Physical Education and Physiotherapy, Katholieke Universiteit Leuven, B-3001 Leuven, Belgium The effect of creatine (Cr) supplementation on muscle isometric torque generation and relaxation was investigated in healthy male volunteers. Maximal torque (Tmax), contraction time (CT) from 0.25 to 0.75 of Tmax, and relaxation time (RT) from 0.75   to 0.25 of Tmax were measured during 12 maximal isometric 3-s elbow flexions interspersed by 10-s rest intervals. Between the pretest and the posttest, subjects ingested Cr monohydrate (4   × 5 g/day; n  = 8) or placebo ( n  = 8) for 5 days. Pretest Tmax, CT, and RT were similar in Cr and placebo groups. Also in the posttest, Tmax and CT were similar between groups. However, posttest RT was decreased consistently by ~20% ( P  < 0.05) in the Cr group from the first to the last of the 12 contractions. In addition, the mean decrease in RT after Cr loading was positively correlated with pretest RT ( r  = 0.82). It is concluded that Cr loading facilitates the rate of muscle relaxation during brief isometric muscle contractions without affecting torque production. exercise; phosphocreatine; diet; contraction